Gizi Ibu Hamil : Coaching Menu Sehat dan Pola Makan Seimbang Berbahan Lokal Daun Kelor pada Ibu Hamil di Wilayah Kerja Puskesmas - Lina Fitriani; Rosita; Nunung Erviany; Dyah Tahir (Asosiasi Riset Ilmu Tanaman Dan Hewan Indonesia, 2025)
The pregnancy period is a crucial time for ensuring the health of the mother and fetus through the provision of balanced nutrition. However, nutritional issues such as anemia and chronic energy deficiency (CED) are still commonly found among pregnant women. The use of local nutritious foods, such as moringa leaves (Moringa oleifera), can be a potential solution to support nutritional needs. This community service activity aims to improve the knowledge and skills of pregnant women in preparing healthy menus and balanced eating patterns using moringa leaves. The activity was carried out through interactive lectures, coaching on menu preparation, cooking demonstrations of moringa leaf dishes, and evaluation through pre-tests and post-tests. The participants were pregnant women in the working area of the Wara Selatan Health Center in Palopo City, totaling 25 people. The results showed an increase in participants' nutritional knowledge, with an average pre-test score of 55 rising to 82 in the post-test. Participants were also able to prepare a balanced daily menu based on moringa leaves and produce several processed products, including moringa soup, moringa fritters, and moringa pudding. It can be concluded that the healthy menu coaching activity using local moringa leaves effectively improves the knowledge and skills of pregnant women regarding balanced nutrition. The use of local foods such as moringa leaves has the potential to support the improvement of maternal nutritional status in a simple, economical, and sustainable manner.